Soil, Crop Yield, and Economic Benefits of Conservation Agriculture-Based Cropping Systems: Triple Wins during an El Niño-Induced Drought Year in Zimbabwe - MASHAVAKURE, NILTON; Soropa, Gabriel; Mandityira, Caroline R; Chivhuna, Primrose; Musiyiwa, Kumbirayi (Plantropica: Journal of Agricultural Science, 2025)
Conservation agriculture (CA) is a sustainable farming system that can confer agronomic, ecological, and economic benefits to farmers across the globe. This study evaluated the effects of different cropping systems on soil properties, crop and fodder yields, and economic returns. Data was collected from a four-year-old experiment at Chinhoyi University of Technology farm with seven treatments [no-till (NT), NT + dead mulch (DM), NT + live mulch using Brachiaria and Desmodium uncinatum (LM), NT + rotation (ROT), NT + DM + ROT, NT + LM + ROT and conventional tillage (CT)] in a randomized complete block design with three replications. Compared to CT, NT + LM + ROT reduced soil bulk density by 5.6% and increased water-holding capacity by 49.8%. Soil organic matter was lowest in CT (1.8%), and highest in NT + DM + ROT (5.5%). CT also resulted in lower soil pH (5.6) than NT-based systems (pH = 6.4-7.2). While NT + LM + ROT improved bulk density and water-holding capacity, NT + DM + ROT enhanced soil organic matter. NT + DM increased maize and soybean yields by 31.8% compared to CT, whereas NT and NT + LM reduced yields by 58.5-91.3%. Despite these yield differences, NT systems with DM or LM exhibited 37.4% lower total variable costs and greater economic performance than both CT and NT. These findings demonstrate the potential of CA to improve soil health, enhance financial returns, and boost yield, offering a sustainable alternative for agricultural production.